Inovasi Desa Mandiri: Integrasi Agile Governance dan Pembangunan Berkelanjutan dalam Tata Kelola Pedesaan - Rasaili, Wilda; Suharyanto, Deny Feri; Andiriyanto, Ach; Fitriyah, Nina Sa’idah; Zarnuji; Puspaningrum, Irma Irawati (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2024)
This research aims to explain Independent Village Innovation through the integration of agile governance and sustainable development in village governance. The main focus of the research is on the efforts of the governments of Lobuk Village, Sumenep Regency, East Java and Srimulyo Village, Bantul Regency, Yogyakarta in development innovation through the principles of agile governance. The agile governance approach emphasizes the responsiveness and flexibility of governments that move quickly and agilely in administering government, services and development. Qualitative research method with a case study approach. Data were collected through in-depth interviews, policy document analysis, and participatory observation. The number of informants was 10 people, including village heads, village officials, businesspeople, village youth, community leaders, and experts in policy and development. The results of the study explain the success of village development innovation through the integration of agile, adaptive, and sustainable governance. The agile governance approach encourages a flexible and responsive government in meeting public needs and implementing development. The achievements that have been made are service digitization, high community participation, economic growth, education improvement, infrastructure fulfillment, and accessibility of public mobilization. This research has implications as a guide for village governments in optimizing development strategies to achieve sustainable goals at the local level.